UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN MELALUI STRATEGI PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAM GAME TURNAMEN (TGT) - Etin Solihatin (Jurnal Ilmiah Mimbar Demokrasi, 2013)
The purpose of this research is to improve learning outcomes through Cooperative Learning Civics Team Type Game Tournament (TGT) and promote cooperation among the students. Research methods Classroom Action Research by 3 cycles. The results of the study in the first cycle an average score of 62.6 students, with an increase of 12.64%. Cycle II scores an average of 74.07, with a gain of 33.21%. Cycle III students' average scores amounted to 82.9, with an increase of 49.16%. Type TGT Civics can improve learning outcomes by 49.16%. So learning outcomes Civics increased by 49.16% by using Cooperative Learning Type TGT.